The impact of Hilda Taba's model on the collection of grammatical concepts among primary school students (Journal of the College of Basic Education, 2022)
This study was conducted in Amman Primary School for Boys located in Diyala Governorate / Baquba, and aimed to know the impact of Hilda Taba's model on the collection of grammatical concepts among primary school students.The research sample consisted of 54 students, including (27) a student studying Arabic grammar using the Hilda Tapa model and (27) a student studying grammar in the traditional way. At the beginning of the academic year 2013-2014 and it lasted a full semester, and at the end of the experiment, the researcher conducted a post-achievement test for both groups, and the results showed that there was a statistically significant difference at the level (0.05) in favor of the experimental group.